Efeitos da Sazonalidade Sobre o Perfil Mineral em Caprinos Criados no Semiárido - Lima, Joseney Maia de (2015)
Aiming to evaluate the effect of season on the mineral profile of goats, fifty males were divided into two groups, one group had mineral supplementation in their diet and the other was the control group, they were kept in native caatinga pastures in the semiarid region. The seasonal evaluation took place during four periods: end of drought season, middle of rainy season, beginning of the drought season, middle of the drought season. To analyze the accumulation of minerals, biopsies of ribs and liver were performed and blood was sampled in each period. The concentration of calcium (Ca), phosphorus (P), copper (Cu), iron (Fe), molybdenum (Mo), zinc (Zn) and cobalt (Co) was measured through Inductively Coupled Plasma Optical Emission Spectrometry after nitric/perchloric digestion. Levels of calcium and phosphorus in the serum and in the bones were within normality in both groups at all periods, as well as levels of molybdenum in the serum and in the liver. High levels of iron in the serum and in the liver were observed during all periods. On the other hand, serum concentrations of copper in the control group, at the end of drought season were inside the levels considered critical for deficiency and hepatic levels were deficient throughout all season periods. A hepatic deficiency of zinc was observed at the beginning and in the middle of drought season and serum deficiency of cobalt in the control group at the end of drought season and in the middle of rainy season. It is suggested that a diet with specific mineral supplements, formulated for animals bred in the semiarid region, be supplied to them, allowing cost reduction